Pengaruh Cycling Exercise Terhadap Penurunan Nyeri Pada Osteoarthritis Di Posyandu Lansia Puskesmas Kedungwuni II Kabupaten Pekalongan - Abdurrachman Abdurrachman; Dzikra Nurseptiani; Maushaly Adani (Universitas Muhammadiyah Jember, 2019)
Osteoarthritis is classified as arthritis, which affects 15% of the world's population. Prevalence of osteoarthritis, including the high category of 2.3% to 11.3% is a musculoskeletal disease that often occurs at number 12 among all diseases. Estimated that the prevalence of osteoarthritis has increased doubly in 2020 as the population ages. Symptoms found in osteoarthritis are pain. Osteoarthritis is degenerative disease of the joint due to the breakdown of articular biochemical (hyaline) cartilage in the synovial joint of the knee that joint cartilage damaged. One of the sports that can be done by the elderly is cycling exercise, some of the benefits obtained from cycling exercise are strengthening muscles that function to maintain balance and increase the power of the muscles of the lower extremities by giving effect to blood circulation so that it can reduce the intensity of pain. The sampling technique purposive sampling to get 40 respondents. Quasi experiment design the techniques taken are times series design. The results showed effect of cycling exercise intervention on pain reduction in osteoarthritis which was felt in the elderly with the results ρ = 0,000 or ρ α (0.05) minimum and maximum value pre intervention was 2 and 5 while the minimum and maximum value post intervention 1 and 3.